Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/acp.3685
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced self‐affirmation as a method for reducing eyewitness memory conformity: An experimental examination using a modified MORI technique

Abstract: Summary The manuscript describes an experimental investigation of one possible technique that may reduce memory conformity: the reinforced self‐affirmation procedure (RSA). While previous studies have already demonstrated the RSA's effectiveness in reducing other memory distortions (e.g., the misinformation effect and interrogative suggestibility), this has not been tested in the context of the co‐witness memory conformity effect. To this end, we will utilize the well‐known MORI technique to study co‐witness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…Explorative mediation analyses also showed that the indirect effect of self‐esteem on false memory was significant in Study 1a and Study 2 and the indirect effect of self‐esteem on NBM was significant in Study 2. These results also dovetail with research on self‐esteem and collaborative recall (Kękuś et al, 2020; Szpitalak & Polczyk, 2015, 2019), indicating that self‐esteem may influence the direction of memory contagion through metacognitive appraisal. Individuals with low self‐esteem would hold a more skeptical view of their memory functioning in general, which might make them more vulnerable to memory distortions under certain social influences such as interrogation or misguided interviews.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Explorative mediation analyses also showed that the indirect effect of self‐esteem on false memory was significant in Study 1a and Study 2 and the indirect effect of self‐esteem on NBM was significant in Study 2. These results also dovetail with research on self‐esteem and collaborative recall (Kękuś et al, 2020; Szpitalak & Polczyk, 2015, 2019), indicating that self‐esteem may influence the direction of memory contagion through metacognitive appraisal. Individuals with low self‐esteem would hold a more skeptical view of their memory functioning in general, which might make them more vulnerable to memory distortions under certain social influences such as interrogation or misguided interviews.…”
Section: Discussionsupporting
confidence: 85%
“…significant in Study 1a and Study 2 and the indirect effect of selfesteem on NBM was significant in Study 2. These results also dovetail with research on self-esteem and collaborative recall(Kęku s et al, 2020;Szpitalak & Polczyk, 2015, indicating that selfesteem may influence the direction of memory contagion through…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Similar to Kękuś et al (2020, p. 1203), we will inspect the memory conformity effect using the procedure of Garry et al (2008), also, Ito et al, 2019). Analogously to Garry et al, we will examine the final test accuracy scores for the critical details with the use of analysis of variance (ANOVA).…”
Section: Resultsmentioning
confidence: 99%